QUALITY OF Eucalyptus urograndis CHARCOAL PRODUCED IN THE SOUTHERN REGION OF TOCANTINS - Marchesan, Raquel; Mendonça, Daniela; Caixeta Dias, Ana Carolina; Carvalho da Silva, Renata; Pereira, José Fernando; Almeida, Vanessa Coelho (Floresta, 2019)
The objective of this work was to determine the quality of the Eucalyptus urophilla x Eucalyptus grandis clone charcoal, defining the basic density and wood retractability, apparent density, breaking index, charcoal yield, condensable and non-condensable gas yield, AQI and calorific values, comparing the results of different trunk positions and in two different heating ramps, ramp 1 (R1) with a heating rate of 1.25 ºC/min, final temperature of 450ºC and total of 6 hours, and ramp 2 (R2) with a heating rate of 1.19 ºC/min, final temperature of 500ºC and total time of 7 hours. The six evaluated trees were from a six-year-old cloned tree plantation located in the municipality of Gurupi, in the south of Tocantins state. The specimens for the characterizations were made from wooden discs removed from three trunk positions (base, DBH, top). The Eucalyptus urograndis wood presented basic density considered average (0.47 g/cm³) and good dimensional stability. The charcoal presented an expected yield and high calorific value influenced by the final temperature of the heating ramps, high fixed carbon content, acceptable ash content, as well as a low breaking rate. The results were satisfactory and identified the species as a good energy source.